Effect of drying temperature on quality of β-glucan in white oat grains - Oliveira,Leandro da Conceição (2012)
Oats have received attention because of their nutritional characteristics, especially their high-quality content of β-glucan. The drying process reduces water content; therefore they can be preserved for long periods. However, high-temperature drying process may affect the physical, chemical, and functional properties of the grains. The objective of this study was to evaluate the effect of different drying temperatures on β-glucan quality in oat grains. Grains of oats (Avena sativa, L.), cultivar Albasul, harvested at harvest moisture content of 23% were submitted to stationary drying at air temperatures of 25, 50, 75, and 100 ºC until they reached 13% moisture content. The β-glucan content was determined in samples of oat grains and extraction was performed using water as solvent at 90 ºC. The β-glucan extract was evaluated for water holding capacity, water retention capacity, capacity of displacement, and gelation properties. Stationary of oat grains at air temperatures above 25 ºC decreased the water holding capacity, whereas the content of β-glucan and the water retention capacity of β-glucan extract was affected at temperatures above 50 ºC. Physical changes such as increased gelation capacity of the β-glucan extract occurred following drying at air temperature over 75 ºC.